A dataset for earthworm communities in French Guiana - Goulpeau, Arnaud; Hedde, Mickaël; Maggia, Marie-Eugénie; Gérard, Sylvain; Lapied, Emmanuel; Decaens, Thibaud (Soil Organisms, 2024)
Earthworms represent a crucial taxon in soil ecosystems in terms of biomass and ecological functions. Knowledge of their diversity is growing, but the understanding of the ecological and evolutionary mechanisms underlying this diversity and its distribution patterns remains poorly understood. This is partly due to a lack of community data available on a large scale, particularly in the natural ecosystems of the most diverse tropical regions. Here we describe a large dataset containing records of 3555 georeferenced earthworm specimens, sampled in 125 one-hectare plots distributed in different habitats and localities across French Guiana. Each of these specimens was DNA barcoded targeting the cytochrome C Oxidase I subunit barcode region (COI), and these sequences were clustered into molecular operational taxonomic units (OTUs) that we used as species proxy to describe community taxonomic composition and diversity. Each community is associated in the dataset with climate and elevation data, and soil properties are also available for part of them. This dataset represents a unique opportunity for analyzing community diversity and phylogeographic patterns in neotropical rainforests.
Keywords: Oligochaeta; tropical rainforest; COI barcodes; alpha diversity; beta diversity